Study of intrapartum fetal distress with the help of cardiotocography and its correlation with umbilical cord blood sampling - Neeraja, S.; Parimala, Sugathi; Fathima, Naima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Even in low risk mothers, fetal acidosis occurs as in high risk groups. Aim of fetal monitoring is to detect early response to intrauterine hypoxia and prevent irreversible neurological damage and death. Objective of this study was to correlate the intrapartum fetal distress with the help of cardiotocography CTG with umbilical cord blood sampling. Methods: A total 100 consecutive patients attending the labor ward were studied. Immediately at birth, before the baby’s first breath and before delivery of the placenta, the umbilical cord blood was collected as per the standard guidelines laid down in the standard textbooks. Fetal acidosis was assessed by umbilical cord arterial blood pH. Fetal acidosis was considered when umbilical artery pH <7.2. Cardiotocography features were used to clinically diagnose fetal distress. Results: Most of the mothers were multigravida. They belonged to the age group of 20-25 years. Only 18% had abnormal CTG. Out of 50 mothers with normal vaginal delivery, all had normal CTG. Out of 43 mothers who were delivered by LSCS, no one had normal CTG, 25 had indeterminate CTG and 18 had abnormal CTG. As CTG became abnormal, proportion of mothers with the thick meconium increased. NICU admission proportion increased as CTG changed from normal to the abnormal. There was a significant association between the abnormal CTG and the umbilical cord blood pH being acidic. Conclusions: CTG is a simple test, easy to perform and can alert obstetrician for necessary interventions in case of an abnormal CTG. It can detect fetal distress in labor thus helping to reduce neonatal morbidity by early intervention in cases of abnormal tracing.